1986
DOI: 10.1136/ard.45.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Cytidine deaminase activity as a measure of acute inflammation in rheumatoid arthritis.

Abstract: SUMMARY Cytidine deaminase (CD), a cytoplasmic enzyme, is thought to leak out of damaged cells and can be measured in fluids by a simple biochemical assay. This study has shown that serum CD activity is raised in rheumatoid arthritis (RA) compared with osteoarthritis (OA). Synovial fluid (SF) CD activity was always less than the corresponding serum activity (mean SF/serum ratio=0-6) in OA but up to 22 times greater than the corresponding serum activity in RA (mean SF/serum ratio= 13-1), suggesting CD productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…Recent studies have focused on isoenzyme pattern of ADA, which has two isoenzymes: ADA-1 and ADA-2. CD catalyses the hydrolytic deamination of cytidine, deoxycytidine and their analogues (9,10). Although its tissue source is not yet known, it is suggested that the monocyte-macrophage cell system is a major source of ADA-2 in humans (8).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on isoenzyme pattern of ADA, which has two isoenzymes: ADA-1 and ADA-2. CD catalyses the hydrolytic deamination of cytidine, deoxycytidine and their analogues (9,10). Although its tissue source is not yet known, it is suggested that the monocyte-macrophage cell system is a major source of ADA-2 in humans (8).…”
Section: Introductionmentioning
confidence: 99%
“…Since cytidine analogues are widely used, a simple test would be preferred. Moreover, inflammation results in a large variation of CDA activity, leading to the hypothesis that CDA may be a marker of rheumatoid arthritis . Because the variation induced by inflammation may be larger than that caused by a genotype, a phenotypic assay measuring enzyme activity to evaluate fluctuations in CDA activity would be preferable over a genomic assay.…”
mentioning
confidence: 99%
“…In fact, measurement of the ADA activity in peripheral blood cells from normal blood donors shows similar values in lymphocytes and granulocytes (18). In chronic inflammation of the joint, inflammatory cell turnover probably is reflected in certain synovial fluid enzyme levels, such as lysozyme (19), lactofenin (20), immunoreactive vasoactive intestinal peptide (21), elastase (22) and cytidine deaminase (23). These enzyme activities correlate with certain cell components of the local inflammatory response.…”
Section: Discussionmentioning
confidence: 98%